2022
DOI: 10.1186/s12913-022-08225-6
|View full text |Cite
|
Sign up to set email alerts
|

Identifying drivers of health care value: a scoping review of the literature

Abstract: Background As health care spending reaches unsustainable levels, improving value has become an increasingly important policy priority. Relatively little research has explored factors driving value. As a first step towards filling this gap, we performed a scoping review of the literature to identify potential drivers of health care value. Methods Searches of PubMed, Embase, Google Scholar, Policy File, and SCOPUS were conducted between February and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…To create sustainable change, it will be important to target low-value health service drivers broadly. As shown by Landon et al [ 138 ], drivers of low-value services are complex and can be found at all levels: hospital, provider, and patient. Financial incentives, culture in the medical community, and intensity of care are especially strong drivers.…”
Section: Discussionmentioning
confidence: 99%
“…To create sustainable change, it will be important to target low-value health service drivers broadly. As shown by Landon et al [ 138 ], drivers of low-value services are complex and can be found at all levels: hospital, provider, and patient. Financial incentives, culture in the medical community, and intensity of care are especially strong drivers.…”
Section: Discussionmentioning
confidence: 99%
“…Whether differences in the combination of specific care elements reflect a tailoring of care to patient characteristics should be examined in future research. Further, investigations of private health insurances and other financial incentives, healthcare cultures, and individual factors in both patients and clinicians (eg, personal beliefs and preferences), may contribute to a fuller understanding of the complex interplay of system, setting, provider and patient-level factors that may influence care delivery 28 29…”
Section: Discussionmentioning
confidence: 99%
“…"More is better" culture: the "more is better" culture has been highlighted as a critical driver of low-value care for both patients and health care providers 6,16,33,34,40,54,59 . Some patients hold perceptions that more care is necessarily better, and thus may demand more care from their health care providers 59 .…”
Section: Social Factorsmentioning
confidence: 99%
“…Fee-for-service payment system: many authors have observed that payment structures emphasizing volume over value, such as the fee-for-service (FFS) payment system, are linked to the provision of low-value care 6,14,16,17,36,39,40,46,47,57,59,[61][62][63][64][65] . The FFS payment system offers a perverse incentive that drives health care providers to provide low-value care 66 .…”
Section: Health Care System Factorsmentioning
confidence: 99%